Analysis of Optimal Treatment Starting Time for Photothermal Therapy Through Analysis of Diffusion Behavior of Gold Nanoparticles - Kim, Donghyuk; Kim, Hyunjung (International Journal of Nanomedicine, 2024)
Introduction: Due to its distinct advantage of non-invasive application in treatment, photothermal therapy (PTT) is being studied by many researchers to reduce the need for surgical incisions. It is characterized by the injection of nanoparticles into biological tissue as photothermal agents (PTAs) which diffuse within the tissue. In this study, the diffusion behavior of various doses of gold nanoparticles (AuNPs) injected into tumor tissues is analyzed and the effectiveness of PTT at each elapsed time after injection is confirmed by numerical analysis. Methods: The diffusion behavior of AuNPs within biological tissues is assessed using the convection-diffusion equation, while the temperature distribution is determined using the Pennes bioheat transfer equation. In addition, the effect of the diffusion behavior of AuNPs on the effectiveness of PTT is quantitatively confirmed by analyzing the temperature distribution in the medium through the apoptotic variable. Numerical simulation parameters are selected with doses ranging from 100 to 400 μg/mL, elapsed time after injection from 1 min to 24 h, and laser power ranging from 0 to 1 W. Results: After evaluating PTT’s efficacy in every situation, it was discovered that a dosage of 100–300 μg/mL produced the best therapeutic result, with the highest impact occurring 12 hours after injection. In contrast, when the dosage was 400 μg/mL, the highest therapeutic effect was achieved after 18 hours post-injection. Additionally, it was discovered that the ideal laser power at each injection dose was 0.22, 0.14, 0.12, and 0.12 W, respectively. Conclusion: The conditions required to achieve the optimal treatment effect at each dosage, presented here, are expected to accelerate the commercialization of PTT.
Keywords: Cell Line, Tumor; Gold; Hyperthermia, Induced; Metal Nanoparticles; Phototherapy; Photothermal Therapy; apoptosis; elapsed time after injection; gold nanoparticles; injection dose; photothermal therapy; thermal damage